(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This research examines the dialectology and dialects of the English language. The paper analyzes the theoretical and methodological foundations of dialectology, as well as the various dialects of English and their social, cultural, and linguistic aspects.